Chitotriosidase (CHIT1) is increased in microglia and macrophages in spinal cord of amyotrophic lateral sclerosis and cerebrospinal fluid levels correlate with disease severity and progression. Issue 3 (15th November 2017) - Steinacker, Petra; Verde, Federico; Fang, Lubin; Feneberg, Emily; Oeckl, Patrick; Roeber, Sigrun; Anderl-Straub, Sarah; Danek, Adrian; Diehl-Schmid, Janine; Fassbender, Klaus; Fliessbach, Klaus; Foerstl, Hans; et al.
Abstract : Objectives: Neurochemical markers of amyotrophic lateral sclerosis (ALS) that reflect underlying disease mechanisms might help in diagnosis, staging and prediction of outcome. We aimed at determining the origin and differential diagnostic and prognostic potential of the putative marker of microglial activation chitotriosidase (CHIT1). Methods: Altogether 316 patients were included, comprising patients with sporadic ALS, ALS mimics (disease controls (DCo)), frontotemporal lobar degeneration (FTLD), Creutzfeldt-Jakob disease (CJD), Alzheimer's disease (AD), Parkinson's disease (PD) and healthy controls (Con). CHIT1 and neurofilament levels were determined in cerebrospinal fluid (CSF) and blood and analysed with regard to diagnostic sensitivity and specificity and prognostic performance. Additionally, postmortem tissue was analysed for CHIT1 expression. Results: In ALS, CHIT1 CSF levels were higher compared with Con (p<0.0001), DCo (p<0.05) and neurodegenerative diseases (AD p<0.05, PD p<0.01, FTLD p<0.0001) except CJD. CHIT1 concentrations were correlated with ALS disease progression and severity but not with the survival time, as did neurofilaments. Serum CHIT1 levels were not different in ALS compared with any other study group. In the spinal cord of patients with ALS, but not Con, AD or CJD cases, CHIT1 was expressed in the corticospinal tract and CHIT1 staining colocalised with markers of microglia (IBA1) and macrophages (CD68). Conclusions: CHIT1 concentrations in the CSF of patients with ALS may reflect the extent of microglia/macrophage activation in the white matter of the spinal cord. CHIT1 could be a potentially useful marker for differential diagnosis and prediction of disease progression in ALS and, therefore, seems suitable as a supplemental marker for patient stratification in therapeutic trials.